2020
DOI: 10.1021/acsbiomaterials.9b01794
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation and Storage of Therapeutic Fibrin-Homing Peptides using Conducting Polymer Nanoparticles for Programmed Release by Electrical Stimulation

Abstract: CREKA (Cys-Arg-Glu-Lys-Ala) is an important fibrin-homing pentapeptide that has been extensively demonstrated for diagnoses and therapies (e.g. image diagnosis of tumors and to inhibit tumor cell migration and invasion). Although CREKA-loaded nanoparticles (NPs) have received major interest as efficient biomedical systems for cancer diagnosis and treatment, almost no control on the peptide release has been achieved yet. Herein, we report the development of conductive polymer (CP) NPs as therapeutic CREKA carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 61 publications
(224 reference statements)
1
22
0
Order By: Relevance
“…[ 17 ] Furthermore, this conducting polymer was found to be very effective for the electro‐stimulated release of encapsulated drugs. [ 18,19 ] A representative and common antibiotic, CAM, was loaded into the PEDOT NPs. In this work, unloaded PEDOT NPs (control) and CAM‐loaded PEDOT NPs (hereafter PEDOT/CAM NPs) were prepared by in situ emulsion polymerization as shown in Scheme (details are provided in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 17 ] Furthermore, this conducting polymer was found to be very effective for the electro‐stimulated release of encapsulated drugs. [ 18,19 ] A representative and common antibiotic, CAM, was loaded into the PEDOT NPs. In this work, unloaded PEDOT NPs (control) and CAM‐loaded PEDOT NPs (hereafter PEDOT/CAM NPs) were prepared by in situ emulsion polymerization as shown in Scheme (details are provided in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously described that PEDOT NPs can act as excellent therapeutic molecule carriers and attain successful electronic triggered release. [ 18,19 ] However, the encapsulation efficiency for small molecules is challenging, usually leading to low values. In this case, the LC was 11.9 ± 1.3%, which was expressed as mass of loaded CAM with respect to the total mass.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They delivered an effective dose of verapamil, and concluded that electroosmosis would be safer and more reliable if delivered with high systemic toxicity [ 34 ]. A recent study shows that electrical stimulation can control the rate of peptide release, especially fibrin peptides used for tumor image diagnosis and inhibition of tumor cell migration, displaying a wide space for electrical stimulation therapy [ 35 ]. In fact, the PDP method is the mature therapy in iontophoresis, and local delivery greatly reduces adverse reactions such as skin polarization and redness, and systemic delivery is better than oral and injection.…”
Section: Tdds Of Micro-current Stimulationmentioning
confidence: 99%
“…Stimuli‐responsive drug delivery systems potentially enable the treatment of such conditions because they have potential for spatiotemporally controlled drug delivery 8 . Indeed, materials responding to stimuli (such as enzymes, light, pH, temperature, ultrasound and electric/magnetic fields) have been developed for use as drug delivery devices, 9–24 with reviews specifically on the application of electroactive materials for drug delivery 25–31 …”
Section: Introductionmentioning
confidence: 99%